Study of the prevalence of urinary tract infection in febrile children - M., Mathivanan; K., Visalakshi (International Journal of Contemporary Pediatrics, 2018)
Background: Children with fever comprise a major proportion of our practice in outpatient department of Paediatric. The emphasis on identification of urinary tract infections in febrile children is minimal. Very often, children receive antibiotics empirically, without any adequate evaluation for urinary tract infection. The objective of our study is to determine the prevalence of urinary tract infection in all febrile children from 2 months to 5 years of age. Methods: Prospective cross sectional, descriptive study done at Dept of Paediatrics, in a tertiary care centre of South India over a period of 1 year. Children who fulfilled the inclusion criteria were included and demographic details, physical examination and laboratory investigations were done. Statistical analysis was done using SPSS version 18. Results: The study included 200 children. The mean age group of the total population was 2 years 6 months. Females were 105 (53%) and males were 95 (47%). The total prevalence of UTI cases were 9%. The incidence in < 1 year was 11.5%, 1-2 years was 10.6 % and >2 years was 7.14 %. The prevalence of UTI was higher among females (5.5%) than males (4%). Among the 19 UTI cases only 2 cases were without any underlying foci of infection the remaining 17 cases had a definite source of infection. E. coli followed by Klebsiella were found to contribute the maximum number of cases. Conclusions: Possibility of Urinary Tract Infection must be considered in all febrile children and urine culture specimen must be collected as a part of diagnostic evaluation.